Efektifitas Model Pembelajaran Collaborative Learning Berbasis Catur Paramita Terhadap Pemahaman Mahasiswa Pada Teks Geguritan - I Gusti Agung Rai Jayawangsa; I Wayan Juliana (Jurnal Penelitian Agama Hindu, 2026)
Geguritan, as an integral part of Balinese literature taught in higher education, plays a strategic role in preserving identity and passing down noble cultural values to the younger generation. However, based on observations conducted on students of the Balinese Language and Religious Literature Education Study Program, it was found that student understanding of the meanings embedded within geguritan texts remains relatively low. This study aims to determine the effectiveness of implementing a catur paramita-based collaborative learning model in improving students' comprehension of geguritan texts. This study employed a quantitative method with a Pre-Experimental Design, conducted on sixth-semester students as research subjects. The results demonstrated that the average pre-test score of 75.00 increased to an average post-test score of 88.00. Furthermore, the hypothesis testing using a paired sample t-test yielded a significance value of (p<0.001). In conclusion, the implementation of catur paramita-based collaborative learning is effective in enhancing students' understanding of the meanings contained in geguritan texts.